2004
DOI: 10.1161/01.cir.0000138192.65015.45
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Recurrent Ischemic Mitral Regurgitation After Annuloplasty

Abstract: Background-Patients who undergo ring annuloplasty for ischemic mitral regurgitation (MR) often have persistent or recurrent MR. This may relate to persistent leaflet tethering from left ventricle (LV) dilatation that is not relieved by ring annuloplasty. Therefore, the purpose of this study was to test the hypothesis that recurrent MR in patients after ring annuloplasty relates to continued LV remodeling. Methods and Results-Serial echoes were reviewed in 30 patients (aged 72Ϯ11 years) who showed recurrent MR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
167
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(179 citation statements)
references
References 49 publications
8
167
1
3
Order By: Relevance
“…However, increased sphericity of the LV seems to be a maladaptive process because it increases wall stress, leads to greater LV remodeling, and is associated with poor clinical outcomes. [22][23][24][25][26] Echocardiographic measurement of LV mass estimation is performed using area-length method or truncated ellipsoid method. Using any of these 2D methods, the normal LV mass is defined as ≤88 g/m 2 in women and ≤102 g/m 2 in men.…”
Section: Assessment Of LV Mass and Geometrymentioning
confidence: 99%
“…However, increased sphericity of the LV seems to be a maladaptive process because it increases wall stress, leads to greater LV remodeling, and is associated with poor clinical outcomes. [22][23][24][25][26] Echocardiographic measurement of LV mass estimation is performed using area-length method or truncated ellipsoid method. Using any of these 2D methods, the normal LV mass is defined as ≤88 g/m 2 in women and ≤102 g/m 2 in men.…”
Section: Assessment Of LV Mass and Geometrymentioning
confidence: 99%
“…Numerous studies [23, 24,74,75,76,77,78,79,80,81,82,83] have reported a high rate of persistent and/or recurrent MR following restrictive MVA with an exponential relationship between the prevalence of postoperative MR and the length of follow-up (fig. 8).…”
Section: Treatment Of Ischemic Mrmentioning
confidence: 99%
“…Postoperative persistence or recurrence of MR, even if only mild, should not be considered benign, because this residual MR contributes to negative LV remodeling, which leads to a ‘vicious circle’ [74] where MR begets more MR. To this effect, 2 recent studies [23, 78] demonstrated that the presence of persistent or recurrent MR is associated with markedly worse outcomes.…”
Section: Treatment Of Ischemic Mrmentioning
confidence: 99%
“…Undersized annuloplasty with complete ring, associated with CABG, presently is the most frequently performed surgical procedure to treat chronic IMR. However, recurrent MR can be expected in 1/3 of patients because of continued LV remodeling [11,12] . There are many reviews about of adding subvalvular procedures to mitral anuloplasty to reduce the tenting forces and improve the long-term repair results [13][14][15] .…”
Section: Open Controversial On Surgical Managementmentioning
confidence: 99%
“…In particular, recent research efforts concentrated on exercise echocardiography [5,30] . Hung et al [11] , for example, demonstrated as CABG alone left more patients with heart failure symptoms at rest and during exercise. This diagnostic tool should always be considered preoperatively because induced dyspnea, increased in MR severity and systolic pulmonary artery pressure are often disguised in patients with moderate IMR at rest.…”
Section: Future Perspectivesmentioning
confidence: 99%